Enhancing Teacher Professionalism through Academic Supervision: An Investigation in Remote and Peripheral Regions - Tami Nurhadi; Ali Imron; Teguh Triwiyanto (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This research aims to describe academic supervision by the school principal to enhance the professionalism of teachers in remote and disadvantaged areas. This study utilizes a qualitative approach to understand the specifics experienced by the subjects in this research. Data collection techniques involve observation, interviews, and documentation. Data analysis is conducted through data condensation, data display, and conclusion. Based on the research findings, the implementation of academic supervision by the school principal begins with pre-supervision meetings. Subsequently, comprehensive classroom observations are carried out objectively using academic supervision instruments, concluding with post-supervision meetings to provide constructive feedback to the teachers. The impact of implementing academic supervision by the school principal includes an increase in teachers' competence in carrying out Teaching and Learning Activities, heightened creativity and innovation in the use of teaching methods and learning media, and an increase in teachers' confidence and collaborative attitudes. In addressing obstacles, the efforts made by the school principal include dividing the tasks of academic supervision among the vice principal and trained senior teachers, scheduling academic supervision at times when technical disruptions are minimal, employing a persuasive approach with teachers, and providing an understanding of the goals and benefits of supervision along with examples of successful instances of academic supervision to teachers. Thus, the implementation of academic supervision by the school principal can enhance teachers' pedagogy, personality, social attitudes, and professionalism in schools in remote and disadvantaged areas.